Responsible biophilia for zoonosis prevention through a cultural lens - Li, Hongying (Frontiers in Conservation Science, 2025)
Human affinity for nature (“biophilia”) brings substantial health and ecological benefits and fosters environmental stewardship. However, close human-nature interactions can lead to conservation challenges and increase the risk of zoonoses. This paradox raises critical questions about how to balance public health, biodiversity conservation, and sustainable development, and understanding these dilemmas presents opportunities for integrated approaches seeking synergies rather than trade-offs. This perspective explores the complexities of these intricate challenges by examining cases that demonstrated the interconnections between biophilia and zoonotic risks and their implications for conservation, public health, and local livelihood. Acknowledging the role of social and cultural perspectives in shaping human-nature interactions, this perspective highlights the importance of integrating traditional knowledge and practices and tailored risk communications into community-centered initiatives for zoonotic risk mitigation. The discussion proposes a responsible biophilia approach that embraces biodiversity conservation as a primary strategy for zoonosis prevention. By fostering responsible biophilia through a transdisciplinary and culturally relevant approach, we can align conservation, public health, and sustainable local livelihood, transforming biophilia-based human-nature interaction into opportunities for community health and resilience.